Valuable antiviral therapeutic options for the treatment of chronic hepatitis C patients with thrombocytopenia. Issue 12 (26th May 2013) - Ogawa, E.; Furusyo, N.; Murata, M.; Ikezaki, H.; Ihara, T.; Hayashi, T.; Toyoda, K.; Okada, K.; Kainuma, M.; Kajiwara, E.; Takahashi, K.; Satoh, T.; et al.
Summary: Thrombocytopenia in patients with chronic hepatitis C may represent an obstacle for the initiation of antiviral treatment. The aim of this study was to evaluate factors predictive of successful pegylated interferon (PEG‐IFN) α2b and ribavirin (RBV) treatment for patients with thrombocytopenia with no history of splenectomy or partial splenic embolization. One hundred and fifty‐one chronic hepatitis C patients (genotype 1: n = 110, genotype 2: n = 41) with TCP (<100 × 10 9 /L) at baseline were enrolled. Pretreatment variables included interleukin 28B (IL28B) genotype (rs8099917) and homoeostasis model assessment of insulin resistance score (HOMA‐IR). The kinetics of haemoglobin and platelets according to the inosine triphosphatase (ITPA) genotype (rs1127354) were investigated. Sustained virological response (SVR) was significantly more frequent in hepatitis C virus (HCV) genotype 2 (65.9%) than in genotype 1 (34.5%) patients ( P < 0.0001). Multiple logistic regression analysis of HCV genotype 1 extracted IL28B TT genotype [odds ratio (OR) 5.97, P = 0.006] and HOMA‐IR <2.5 (OR 7.14, P = 0.0016) as significant independent pretreatment predictors of SVR. The analyses of HCV genotype 2 showed that HOMA‐IR was significantly related to SVR, but IL28B genotype was not. Patients with ITPA CC genotype showed a significant haemoglobin reduction and lower degree of platelets decrease than those with ITPA CA/AA genotypes. The most common reason for premature discontinuation of treatment was the development of hepatocellular carcinoma ( n = 8, 5.3%). In conclusion, HOMA‐IR is a useful predictor of SVR for patients with thrombocytopenia infected with HCV genotype 1 or 2 treated with PEG‐IFNα2b and RBV. The inclusion of IL28B, ITPA genotypes and HOMA‐IR adds valuable therapeutic information.